Profitability, Liquidity, Firm Size, Asset Structure and Capital Structure in Food and Beverage Companies Listed in Indonesia Stock Exchange - Fifita Trajuning Arjansi; Siti Nurlaela; Riana Rachmawati Dewi (Journal of Research in Business, Economics, and Education, 2020)
This study aims to examine and analyze the effect of profitability, liquidity, firm size and asset structure on capital structure. The population in this study are all Food and Beverage companies listed on the Indonesia Stock Exchange. This type of research is quantitative research. The sampling method uses a purposive sampling method, so as many as 13 food and beverage companies were obtained which were listed on the Indonesia Stock Exchange in 2013-2018. The data used in this research is secondary data. The results of this study use multiple linear regression analysis techniques. Based on the results of t test research shows that the variable profitability and asset structure affect the capital structure. While the liquidity and company size variables do not affect the capital structure. This research has the benefit to know about the influence of profitability, liquidity, company size and asset structure on capital structure so that it can be one of the factors that the company is feasible or unfit for as a place to invest.